Stable antivortices in multiferroic ε-Fe2O3 with the coalescence of misaligned grains - Wuhong Xue; Tao Wang; Huali Yang; Huanhuan Zhang; Guohong Dai; Sheng Zhang; Ruilong Yang; Zhiyong Quan; Run-Wei Li; Jin Tang; Cheng Song; Xiaohong Xu (Nature Communications)
Abstract Antivortices have potential applications in future nano-functional devices, yet the formation of isolated antivortices traditionally requires nanoscale dimensions and near-zero magnetocrystalline anisotropy, limiting their broader application. Here, we propose an approach to forming antivortices in multiferroic ε-Fe2O3 with the coalescence of misaligned grains. By leveraging misaligned crystal domains, the large magnetocrystalline anisotropy energy is counterbalanced, thereby stabilizing the ground state of the antivortex. This method overcomes the traditional difficulty of observing isolated antivortices in micron-sized samples. Stable isolated antivortices were observed in truncated triangular multiferroic ε-Fe2O3 polycrystals ranging from 2.9 to 16.7 µm. Furthermore, the unpredictability of the polarity of the core was utilized as a source of entropy for designing physically unclonable functions. Our findings expand the range of antivortex materials into the multiferroic perovskite oxides and provide a potential opportunity for ferroelectric polarization control of antivortices.